2007
DOI: 10.1007/s10562-007-9099-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and catalytic performance of Co3O4 catalysts for low-temperature CO oxidation

Abstract: Without use of any surfactant or oxidant, a series of Co 3 O 4 catalysts have been prepared from cobalt nitrate aqueous solution via a very simple liquid-precipitation method with ammonium acid carbonate followed by calcination at various temperatures. The catalytic performance of the Co 3 O 4 for CO oxidation has been studied with a continuous flowing laboratory microreactor system. The results show that the CO conversion of all the samples can reach 100% at ambient temperature. The catalyst calcined at 300°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 45 publications
3
47
0
1
Order By: Relevance
“…Co 3 O 4 has been proven to have high catalytic activity in CO oxidation reaction [5,26]. It is reported that the catalytic activities of the Co 3 O 4 materials strongly depend on their morphologies, crystal sizes, and exposed crystal facets [3,4,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co 3 O 4 has been proven to have high catalytic activity in CO oxidation reaction [5,26]. It is reported that the catalytic activities of the Co 3 O 4 materials strongly depend on their morphologies, crystal sizes, and exposed crystal facets [3,4,27].…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt oxide (Co 3 O 4 ) is a typical transition metal oxide and is widely used in catalytic oxidation reactions [5][6][7][8][9]. However, bulk Co 3 O 4 usually possesses a low surface area (*20 m 2 /g) which is unfavorable to its applications either as a catalyst or as a catalyst support.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Co 3 O 4 -based catalysts, studied several decades ago for the high activity for CO and VOCs oxidation [12][13][14], have received again considerable attention in the last years [15][16][17][18][19][20][21]. Doping ceria with transition metals is known to modify the redox properties, enhancing the oxygen mobility and improving the catalytic activity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As a promising candidate of precious metal catalysts, cobalt oxide catalysts have attracted considerable attentions because of not only its high activity for CO and hydrocarbon oxidation [18,19], but also its use in the Fischer-Tropsch synthesis [20], NO decomposition [21], and ammonia oxidation [22]. The low-temperature CO oxidation over single component, composite and supported cobalt oxide catalysts have been studied [12][13][14][15][16][17][18], and these cobalt oxides show significant catalytic activity for CO oxidation.…”
Section: Introductionmentioning
confidence: 99%